The more important limitation in process design for agricultural products is the lack of information on their thermal properties. Although a lot of experimental data can be found, the variety of product and the differences ij measurement method make limitation on the value of the available data, especially for indonesia'a products. These data are needed to get information about temperature change when product was processed like hetaing or cooling. It is worth to optimize efficiency of energ - Lamhot P Manalu; Kamaruddin Abdullah (PERTETA, 1998)
The more important limitation in process design for agricultural products is the lack of information on their thermal properties. Although a lot of experimental data can be found, the variety of product and the differences ij measurement method make limitation on the value of the available data, especially for indonesia'a products. These data are needed to get information about temperature change when product was processed like hetaing or cooling. It is worth to optimize efficiency of energy. The objective of his study is to predict thermal diffusivity and conductivity of carrot. The value was determined numerically with direct and indirect methods. The result shows that thermal conductivity is 0.626 W/moC while thermal diffusivity are 2.51 x 10- m2/s (indirect method) and 2.08 x 10- 7 m2/s (direct method)